Rubin Observatory LSST transients and variable stars roadmap - Hambleton, Kelly; Bianco, Federica B.; Street, Rachel; Bell, Keaton; Buckley, David; Graham, Melissa; Hernitschek, Nina; Lund, Michael B.; Mason, Elena; Pepper, Joshua; Prša, Andrej; Rabus, Markus; et al. (Publications of the Astronomical Society of the Pacific, 2023)
The Vera C. Rubin Legacy Survey of Space and Time (LSST) holds the potential to revolutionize time domain astrophysics, reaching completely unexplored areas of the Universe and mapping variability time scales from minutes to a decade. To prepare to maximize the potential of the Rubin LSST data for the exploration of the transient and variable Universe, one of the four pillars of Rubin LSST science, the Transient and Variable Stars Science Collaboration, one of the eight Rubin LSST Science Collaborations, has identified research areas of interest and requirements, and paths to enable them. While our roadmap is ever-evolving, this document represents a snapshot of our plans and preparatory work in the final years and months leading up to the survey’s first light.